Ideal, Norm, and Law - Sebastian Baryli (The European Journal of Psychoanalysis, 2024)
The inherent contradiction of the concept of ideal shows the gap between the imaginary and symbolic levels of ideals. In the confrontation with the other/Other, there are two paths for the subject. One path leads to a more symbolic ideal and law, the other path ends in an imaginary game of norms. Considering Foucault’s thesis about the historical transformation from a society of sovereignty to a society of normativity, norms are becoming more important. Alongside the logical analysis of the subject positions, a dialectical understanding provides an opportunity to understand the link between law and emancipation. This understanding has implications for psychoanalysis and its clinical applications.
Keywords: law; Ideal; Ideal Ego; Ego Ideal; Norm